2021
DOI: 10.1002/eap.2279
|View full text |Cite
|
Sign up to set email alerts
|

Water storage decisions will determine the distribution and persistence of imperiled river fishes

Abstract: Managing the world’s freshwater supply to meet societal and environmental needs in a changing climate is one of the biggest challenges for the 21st century. Dams provide water security; however, the allocation of dwindling water supply among reservoirs could exacerbate or ameliorate the effects of climate change on aquatic communities. Here, we show that the relative sensitivity of river thermal regimes to direct impacts of climate change and societal decisions concerning water storage vary substantially throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
99
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(100 citation statements)
references
References 23 publications
1
99
0
Order By: Relevance
“…Given the potential for seasonal migratory behavior in Schizothorax [73, 127], hydropower dams will disrupt movements, thus inadvertently promoting interspecific contact. Here, we again emphasize parallels with the heavily-modified and regulated rivers of western North America, where water policy and impoundments promote hybridization [122, 128], define habitat suitability [129], and alter environmental cues [130]. Though both countries have a high percentage of protected areas, our results suggest that anthropogenically-mediated hybridization represents an additional dimension to consider when balancing freshwater conservation planning [131, 132].…”
Section: Discussionmentioning
confidence: 64%
“…Given the potential for seasonal migratory behavior in Schizothorax [73, 127], hydropower dams will disrupt movements, thus inadvertently promoting interspecific contact. Here, we again emphasize parallels with the heavily-modified and regulated rivers of western North America, where water policy and impoundments promote hybridization [122, 128], define habitat suitability [129], and alter environmental cues [130]. Though both countries have a high percentage of protected areas, our results suggest that anthropogenically-mediated hybridization represents an additional dimension to consider when balancing freshwater conservation planning [131, 132].…”
Section: Discussionmentioning
confidence: 64%
“…Higher temperature could hence lead to longer periods of desiccation in the by-passed river channels downstream of hydropower reservoirs (Poole & Berman, 2001;Renöfält et al, 2010;Vander Vorste et al, 2020), diminished access to thermal refugia (Fullerton et al, 2018), reduced oxygen concentration in the hyporheic zone, which will affect both trout reproduction as well as invertebrates communities (Calles et al, 2007), and increased water temperatures caused by the release of warm surface waters from hydropower reservoirs and small dams (Lessard & Hayes, 2003;Zaidel et al, 2021). Also, a warmer climate can favour the arrival of invasive species, potentially exacerbating predation and competition on brown trout populations (Daufresne & Boët, 2007;Dibble et al, 2020;Wenger et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…temperatures, together with changes in water storage, may favour the expansion of warm-water non-native species at the expenses of native species, as some parts of the river basin get warmer (Dibble et al, 2020). Another study has shown that river regulation for hydropower interacts with local anthropogenic stressors, such as loss of connectivity and riparian degradation, to affect fish community diversity and composition in bypassed reaches downstream of dams (Göthe et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although strategies may vary by system, in streams and rivers thermal regimes downstream of dams may be improved by variable depth (and hence temperature) water releases that mimic seasonal patterns (i.e., natural thermal regimes; Olden and Naiman 2010), and can be cooled by protecting and increasing riparian vegetation that provides shade from direct solar radiation (Lawrence et al 2014). Water policy decisions that allocate water among reservoirs can alter downstream thermal regimes and may be used as a tool to discourage non‐native fish invasion into critically important habitats (Dibble et al 2021). Improving the physical diversity of river and stream habitats by re‐establishing linkages with floodplains and enhancing in‐channel complexity with large woody debris may provide greater exchange with cooler hyporheic waters and microrefugia for fish use during periods of extreme heat.…”
Section: Warming Water Temperaturesmentioning
confidence: 99%